A CRITICAL DISCOURSE ANALYSIS OF HILLARY CLINTON’S SELECTED TWEETS - Yunita Marpaung; Masdiana Lubis; Rohani Ganie (Program Studi Akuntansi IKOPIN, 2021)
This study aims to find out the text structure, social cognition, and social context used in Hillary Clinton’s selected tweets regarding Critical Discourse Analysis. The selected tweets were taken from Hillary Clinton’s personal account concerning transgender issues. This study used a descriptive qualitative method by applying Dijk’s Critical Discourse Analysis theory (2008) focusing on the socio-cognitive approach. Using a three-leveled analysis, the data were analyzed from textual, socio-cognitive, and social context perspectives. The findings showed the global meaning of Hillary’s tweets is equal right for transgender people or community. From the analysis of superstructure there are three types of structure found (argumentative, narrative, and descriptive). In microstructure analysis, there are four elements of semantics found (setting, detail, intent, and prejudice) and five elements of syntax (pronouns, cohesion, substitution, references, and conjunction). Scheme of event, self-scheme, and role-scheme were found in the social cognition analysis to provide arguments to support transgender community. Access of media, social elites, political elites, and transgender people were found in the social context analysis.